Design of a Web-Based Point of Sale System for Transaction Recording at Sumber Rejeki Store - Agatha Ayu Amalia; Endang Supriyati; Tri Listyorini (SAGA: Journal of Technology and Information System, 2025)
The use of manual transaction recording in Micro, Small, and Medium Enterprises (MSMEs) often causes data inaccuracies, inefficient transaction processes, and difficulties in inventory monitoring. Toko Sumber Rejeki Karangbener Kudus is an MSME that still applies handwritten sales records, leading to limited transaction documentation and delayed reporting. This study aims to design a web-based Point of Sale (POS) system to support sales transactions, inventory management, and sales reporting. The study employs a Research and Development (R&D) approach using the Waterfall model. Data were collected through observation of transaction activities, interviews with the store owner, and a literature review related to POS systems and MSME digitalization. System design was carried out using structured modeling, including use case diagrams, activity diagrams, data flow diagrams, entity relationship diagrams, sequence diagrams, and user interface design. The developed system provides role-based access for cashiers, administrators, and owners. Cashiers handle sales transactions and cash sessions, administrators manage product and stock data, and owners monitor sales reports. The proposed system is expected to reduce recording errors, streamline transaction processes, and improve data organization, serving as a practical solution for MSMEs transitioning from manual to digital transaction recording.